IMPLEMENTATION OF THE HILL CHIPHER ALGORITHM IN HIDING MESSAGES - Huda, Miftahul (Fakultas Ushuluddin, Adab, dan Dakwah UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to create a text message encryption program in electronic mail (email) with a Hill Chipher algorithm to maintain the confidentiality of text messages in electronic mail (email) so that they cannot be known by unauthorized persons (unauthorized persons), as well as make it easier for users to send electronic mail (email) confidentially and privately. The Hill Chipher algorithm was used in this study, and the software used was Visual Basic.net for the programming language and Microsoft Visio 2003 for the flowchart. The system development method used is Prototype. The final result of this research is that it is expected to form an email security application in the form of text data, so that it can further complicate the activities of cybercrime perpetrators.